Early Recanalization Postintravenous Thrombolysis in Ischemic Stroke with Large Vessel Occlusion: A Digital Subtraction Angiography Study. (11th May 2016) - Mao, Yi‐Ting; Mitchell, Peter; Churilov, Leonid; Dowling, Richard; Dong, Qiang; Yan, Bernard
Summary: Aims: We aimed to evaluate early recanalization postintravenous (i.v.) tissue plasminogen activator (t‐PA) by digital subtraction angiography (DSA) in acute ischemic stroke (AIS) with large vessel occlusion (LVO). Methods: We performed baseline CT angiography to identify LVO in AIS. Recanalization pre‐ and post‐intra‐arterial therapy (IAT) was categorized to none, partial, and global recanalization (GR). Modified Rankin Scale score ≤2 at 3 months was considered a favorable outcome. Results: Among 1610 patients with AIS, 286 received IV t‐PA. Of these, 55 patients with LVO were included. The median time from IV t‐PA to DSA was 120 min (interquartile range, 79–152). Recanalization post‐IV t‐PA was observed in seven patients (12.7%). By occlusion sites, the recanalization rates were as follows: extracranial internal carotid artery 2 of 14 (14.3%); intracranial internal carotid artery 3 of 24 (12.5%); M1 of middle cerebral artery 3 of 39 (7.7%); M2 of middle cerebral artery 1 of 40 (2.5%); vertebral artery 0 of 4; and basilar artery 0 of 7. GR post‐IAT was associated with favorable outcomes (odds ratio: 8.6; 95% confidence interval, 1.5–48.0; P = 0.014). Conclusion: Early recanalization assessed by DSA post‐IV t‐PA is rarely observed in acute ischemic stroke patients with LVO.